Heat transfer through horizontal microtube of nanofluids under magnetic field for thermal analysis systems - Abadeh, Abazar; Farahani, Somayeh Davoodabadi; Barani, Ehsan; Öztop, Hakan Fehmi (Elsevier, 2023)
According to the increasing desire towards heat transfer rate enhancement with various methods in different industries, this has been an interesting topic of many researchers. The effects of adding TiO2 and Al2O3 nano-particles to water on heat transfer and fluid flow characteristics are investigated with a semi-analytical method in this study. Two nanofluids flow and heat transfer in a microtube are studied in presence of slip boundary con-ditions and magnetic fields. The nanoparticles volume fraction, magnetic fields strength, slip parameter and NBT coefficient (the ratio of Brownian to thermophoretic diffusions) effects on the nanoparticle's distribution, ve-locity profile, temperature distribution and heat transfer coefficient are studied. Furthermore, using the ther-mophysical characteristics of two nanofluids containing TiO2 and Al2O3 nanoparticles, their behavior under different conditions has been investigated. Results are compared with those of other researchers and acceptable similarity is obtained. It was observed that the heat transfer coefficient is increased by the NBT coefficient, magnetic field strength, and slip parameter, and it decrease by the nanoparticles volume fraction. The Nusselt number maximum augmentation of 33% is reported by applying magnetic field. The heat transfer coefficient average for Al2O3/water nanofluid is approximately 20% more than the average of TiO2/water nanofluid.
Keywords: Nanofluid; Microtube; Magnetic field; Slip boundary condition; Heat transfer